Modelling energy transfers between systems to support energy knowledge in use. Issue 2 (3rd July 2018) - Nordine, Jeffrey; Fortus, David; Lehavi, Yaron; Neumann, Knut; Krajcik, Joe
ABSTRACT: School instruction is critical for helping students use energy as a lens for making sense of phenomena, however, students often struggle to see the usefulness of energy analysis for interpreting the world around them. One reason for this may be an over-reliance on the idea of energy forms in introductory energy instruction, which may unintentionally suppress, rather than prompt, insights into how and why phenomena occur. We argue that an approach to energy instruction that emphasizes energy transfers between systems, and does not require the idea of energy forms, provides students with a more consistent and useful set of tools for interpreting phenomena. Such a perspective requires connecting the energy concept to the notion that fields, which mediate interaction-at-a-distance, are a real physical system that can transfer energy – an idea that is rarely presented in middle school science. We outline an instructional approach in which middle school students learn to interpret phenomena by modelling energy transfers between systems of interacting objects and fields. We argue that this approach presents a more physically accurate picture of energy, helps align energy instruction across disciplines, and supports students in seeing the value of energy as a lens for making sense of phenomena.